Suspended Trace Air-Gap Resonators for Low Loss Superconducting Circuits - Fang, Michael Tianyu (California Institute of Technology, 2020)
Quantum memories and networks for distributed quantum information processing require links between the microwave, mechanical, and optical domains. Coherent integration of long-lived superconducting qubits (SCQs) with optomechanical and photonic devices (OMPDs) remains an outstanding challenge. We present a step towards coherent integration using a suspended trace air-gap resonator (STAR): a superconducting resonator on a silicon-on-insulator (SOI) substrate with the signal trace suspended by silicon tethers above and between galvanically connected ground metal planes. As a result, the electric field energy is closely confined within the microwave structure, yielding lower crosstalk compared to conventional coplanar waveguides (CPW). An order of magnitude improvement in the quality factors for STAR over previous work on SOI is achieved, in a transverse cross-sectional area that is an order of magnitude more compact. Electric field participation in lossy bulk dielectrics, a dominant source of energy leakage in previous measurements of aluminum CPW resonators on SOI, is virtually eliminated in STAR. The loss from the metal-air interface now dominates, but can be reduced by several factors using superconductors with better surface properties. Most importantly, STAR fabrication is compatible with Josephson junction and air-bridge deposition for highly coherent integration of SCQs and OMPDs to realize proposals for quantum information storage and networking.
Keywords: Superconducting; Loss; Suspended; Applied Physics; Circuits; Resonators